Long-Term Assessment of Left Ventricular Ejection Fraction and Mitral Regurgitation Following Takeuchi Repair - Akkaya,Gökmen (2019)
Abstract Objective: This study aimed to evaluate the early operative outcomes and to compare the left ventricle and mitral valve functions after initial Takeuchi repair in patients with anomalous left coronary arising from pulmonary artery (ALCAPA). Methods: Fourteen patients (5 males, 9 females; mean age 4.3 years, ranging from 25 days to 34 years) who were operated for ALCAPA between 2007 and 2018 were included in this study. Data were evaluated retrospectively based on our medical records. Results: Hospital mortality rate was 7.1% (n=1). Thirteen surviving patients were kept in follow-up mean 4.3±3.05 years. When compared to preoperative measurements, both left ventricular ejection fraction (LVEF), (P=0.007) and mitral regurgitation (MR) (P=0.001) significantly improved before discharge. Moreover, LVEF values were improved in the late follow-up, considering early postoperative outcomes, and this alteration was significant (P=0.014). Nevertheless, alteration in the degree of MR among patients did not differ in the long-term follow-up (P=0.180). There was no late-term mortality or need for reoperation among patients. Conclusion: Although some centers prefer to direct implantation in ALCAPA, Takeuchi procedure can be accepted as a reliable method that provides satisfactory long-term results, considering that it aids to improve left ventricle ejection fraction and reduced mitral valve regurgitation.